HUBUNGAN FAKTOR HOST, FAKTOR LINGKUNGAN, DAN STATUS GIZI DENGAN KEJADIAN DEMAM BERDARAH DENGUE DI WILAYAH KERJA PUSKESMAS KAYEN KABUPATEN PATI - Lirin Novitasari; Sri Yuliawati; M. Arie Wuryanto (Jurnal Kesehatan Masyarakat (Undip), 2018)
Background: DHF is an endemic disease, which in a certain period able to cause an outstanding incident (KLB). The Public-Health Centre of Kayen is one of 25 health centers in Pati District with the highest coverage of DHF cases compared to other health centers. The purpose of this study is to analyze the relationship between host factors, environmental factors, and nutritional status to the incidence of DHF in the work area of Kayen Public-Health Center, Pati Regency.Method: Observational analytic study with case control research design. The total sample is 76 respondents with the total sampling method. Data analysis used chi square test with a 95% significance level, and a large risk calculation used the value of Odd Ratio (OR).Results: The results of univariate analysis showed that most of the case and control respondents were ≤11 years old (68.4%), most of the respondents had last education in secondary and high school (73.6%), most of the respondents had jobs as housewives (47.4%), respondents also had poor knowledge (43.4%), 3M practice level was not good (32.9%), did not install wire (81.6%), the existence of a landfill in the respondent's house ( 100.0%), the presence of larvae in the respondent's houses (48.7%), and respondents with thin nutritional status (19.7%).Conclusion: From the results of the study, it can be concluded that there is no relationship between knowledge, presence of net wire, and nutritional status to DHF incidence, while 3M practice (p = 0.015; OR = 3.986) and the presence of larvae (p = 0.012; OR = 3.297) have a relation to the incidence of DHF.